Adsorpsi Amonia dari Limbah Cair Tahu dengan Menggunakan Adsorben Sekam Padi Teraktivasi - Nova Yuliasari; Poedji Loekitowati H (Jurnal Penelitian Sains, 2004)
Research to the study of rice husk as the adsorption ammoniac from tofu liquid waste has been done. Activators having used were H2SO4, NaOH and Na2CO3 whose concentration were varied 5, 10 and 15%. The best activator using the adsorption ammoniac from tofu liquid waste. In the research, conditional optimum were determined from contact time and weight of rice husk. The result gives that the best of activator NaOH 15% with adsorptivy or ammoniac 0,775 mg/g. The finest of optimum condition were got contact time 2 hours and weight of rice husk 1,5 g with resulting in adsorptivity of ammoniac 0,815 mg/g.